Using gravity model to forecast the potential range distance of market share between China and the five central Asian countries for their cross-border e-commerce and relative countermeasures - Huang, Wenya; Irina, Mukambaeva; Yan, Zhang; Leu, Jai-Houng (Edelweiss Applied Science and Technology, 2024)
It is proposed that the development opportunity of ‘One Belt, One Road’ should be grasped and emerging markets should be actively explored; international co-operation in e-commerce should be actively promoted at the national level, so as to create a favorable international regulatory environment for the development of cross-border e-commerce; an all-round, high-efficiency and integrated service system led by the governments of various levels should be constructed to enhance the facilitation of cross-border e-commerce; the construction of cross-border e-commerce logistics infrastructures should be accelerated, and cross-border e-commerce logistics infrastructure should be improved. The government should also speed up the construction of cross-border e-commerce logistics infrastructure, improve the overseas warehousing system and enhance the efficiency of cross-border services; innovate cross-border e-commerce financial services and accelerate the development of blockchain technology; and strengthen the construction of export brands to enhance competitiveness.